Simulation of crack growth in reinforced concrete beams using extended finite element method. (October 2020) - Faron, Adrian; Rombach, Günter Axel
Highlights: The extended finite element method is suitable for the crack propagation analysis of reinforced concrete beams. Numerical simulation with multiple crack initiation gives good results for discrete crack growth. The smeared and discrete analysis of crack growth shows high agreement with experimental results. Abstract: Fracture mechanics and the crack propagation in reinforced concrete members is one of the most important approaches to structural safety analysis. Thanks to powerful software and increasingly fast computers, numerical simulation is well suited to analyse even more complex problems, such as crack growth, quickly and economically. In order to validate these analyses in their application, however, it is still necessary to confirm and compare numerous models of load-bearing and material behaviour by experimental investigations. This paper presents nonlinear numerical simulations of bending and shear crack propagation in reinforced concrete beams without transverse reinforcement. The smeared and discrete crack growth of haunched and non-haunched beams is analysed. Compared are the load deformation behaviour and curves which show the crack width in relation with the applied load without building a notch in the structure. The obtained results are presented with different mesh densities. The tests and the numerical simulations will provide a broad interpretation of crack growth and redistribution of inner forces in concrete members. As numerical method to map discrete cracks the extended finite element method (XFEM) is applied. For validation, the crack patterns of real experiments are compared with the results of the different finite element models up to two crack initiations. The evaluation is based on single span beams under bending and shear. The numerical simulations make it possible to predict the fracture behaviour of concrete members and shows good agreement with the experimental results.